If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -104 + -7x = 10x + 15 Reorder the terms: -104 + -7x = 15 + 10x Solving -104 + -7x = 15 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -104 + -7x + -10x = 15 + 10x + -10x Combine like terms: -7x + -10x = -17x -104 + -17x = 15 + 10x + -10x Combine like terms: 10x + -10x = 0 -104 + -17x = 15 + 0 -104 + -17x = 15 Add '104' to each side of the equation. -104 + 104 + -17x = 15 + 104 Combine like terms: -104 + 104 = 0 0 + -17x = 15 + 104 -17x = 15 + 104 Combine like terms: 15 + 104 = 119 -17x = 119 Divide each side by '-17'. x = -7 Simplifying x = -7
| 2x+12=-38-8x | | y=-32x^2-6x | | y=-32x^2-6x | | y=-32x^2-6x | | 2x^2+30=0 | | 14-10x=74-24x | | -37-7x=7x+20 | | (7z-3)-(4z-11)=47 | | 6t-5=2t-5 | | 266-6x=39x+21 | | 3r+6=18 | | 7x(-2x+3)=0 | | 6x(4x+3)=0 | | 2(2)-3y=-9 | | -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 | | 172-6x=6x+16 | | -(-2x)=(-88) | | 2(x+4)=5x-1 | | 6p+12=4p | | -4x+12=x+17 | | 12-9x=52-16x | | 3x-7=-4x | | 3x-7=-1 | | -x-6=-2 | | (x^2-9)(x+4)=0 | | 18+x=-2 | | X^4+6x=0 | | 5x-7=103 |